Intercultural Contacts 2: Visual Learning, Belief Systems, and the Silk Roads - EAA Editorial Office (Education About Asia, 2021)
The term Asia is both, at one level, geographically accurate, and conceptually useful in understanding specific cultures but at another level, the concept of “Asia” is limiting because of regional and global connections that have existed since antiquity. The focus of the January 2021 EAA Digest Exclusive was intercultural contacts, as is the case with this month’s column. Given the subjects most EAA readers teach, understanding the humanities and social sciences means realizing the power of intercultural contacts.
Keywords: Central Asia; China; China and Inner Asia; Economic History; India; International Relations; Korea; South Asia